2017
DOI: 10.1016/s0960-9776(17)30390-9
|View full text |Cite
|
Sign up to set email alerts
|

Nipple-Areola Complex sensation after nipple sparing mastectomy

Abstract: BACKGROUNDNipple-areola complex (NAC) is a signature of the breast. Preservation of the NAC has a positive impact on patients' satisfaction with cosmetic results and feeling of mutilation. 1 Nowadays, there are still no reconstruction techniques quite as satisfying as the real NAC. Nipplesparing mastectomy (NSM) is developed to optimize es-thetic outcomes. However, the oncologic safety and the postoperative viability of the NAC are important concerns. Welling and Jensen 2 postulated that the origin and progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Te NAC is innervated by a plexus under the areola formed by variations of the second, third, fourth, and ffth intercostal nerves [43]. Tese nerves course through the gland to the posterior surface, increasing the likelihood of injury during resection of retroareolar tissue and making the preservation of the anterior branches more important [8,16]. Te frst report of sensory repair in autologous breast reconstruction used the anterior ramus of the lateral branch of the fourth intercostal nerve, which emerges at the midaxillary line after traveling through the serratus anterior muscle and later reports used the third anterior intercostal nerve, most likely due to the decreased likelihood of injury [12,44,45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Te NAC is innervated by a plexus under the areola formed by variations of the second, third, fourth, and ffth intercostal nerves [43]. Tese nerves course through the gland to the posterior surface, increasing the likelihood of injury during resection of retroareolar tissue and making the preservation of the anterior branches more important [8,16]. Te frst report of sensory repair in autologous breast reconstruction used the anterior ramus of the lateral branch of the fourth intercostal nerve, which emerges at the midaxillary line after traveling through the serratus anterior muscle and later reports used the third anterior intercostal nerve, most likely due to the decreased likelihood of injury [12,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Study characteristics are described in Table1. Of 28 total included studies, twelve (n = 578 patients) used objective measures to evaluate sensitivity, such as monoflament testing which included SWM or von Frey hairs [7][8][9][10][15][16][17][18][19][20][21][22]. Areas of the NAC tested with these flaments are displayed in Figure 2.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…19,30 The procedure itself offers a high level of AS, 31,32 but has downsides, including decreased or absent sensation, local complication such as nipple necrosis, and unnatural reconstruction of the breast. 33,34 With more women surviving breast cancer, it is important for patients to fully understand the positive and negative aspects of the procedure before electing it.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have found NSM to be superior to traditional and skin-sparing mastectomies, 40,41 the hypesthetic and dysesthesic consequences of NSM have been well described. 33,34 Earlier study has also delineated a patient-perceived expectation gap for women undergoing NSM. 34,42 As such, these risk outcomes should be described to patients preoperatively.…”
Section: Discussionmentioning
confidence: 99%